RETOLD: Craft Documentation – as Part of the RETOLD Project - George Tomegea (EXARC Journal)
RETOLD is a project implemented through the Creative Europe program of the European Union, whose main purpose is the creation of standard documentation tools to be used in open-air museums. Along with creating documentation, craft documentation is an important component of the project that is the subject of this article.